The Atomic and Electronic Structure of 0° and 60° Grain Boundaries in MoS2 - Nakanishi, Terunobu; Yoshida, Shoji; Murase, Kota; Takeuchi, Osamu; Taniguchi, Takashi; Watanabe, Kenji; Shigekawa, Hidemi; Kobayashi, Yu; Miyata, Yasumitsu; Shinohara, Hisanori; Kitaura, Ryo (Frontiers in Physics, 2019)
We have investigated atomic and electronic structure of grain boundaries in monolayer MoS2, where relative angles between two different grains are 0 and 60 degree. The grain boundaries with specific relative angle have been formed with chemical vapor deposition growth on graphite and hexagonal boron nitride flakes; van der Waals interlayer interaction between MoS2 and the flakes restricts the relative angle between two different grains of MoS2. Through scanning tunneling microscopy and spectroscopy measurements, we have found that the perfectly stitched structure between two different grains of MoS2 was realized in the case of the 0 degree grain boundary. We also found that even with the perfectly stitched structure, valence band maximum and conduction band minimum shows significant blue shift, which probably arise from lattice strain at the boundary.